Whole-family approach to agricultural market success - Apa, Taaloga; Boto, Isolina; Addison, Chris; Jejov, Emil; Senou, Osseni (Technical Centre for Agricultural and Rural Cooperation, 2019)
This brief describes how Women in Business Development Incorporated (WIBDI), a non-profit organisation in Samoa, works with farming families to produce highvalue products for local and global markets. Shifting away from a women-focused approach, WIBDI now uses an approach that involves the whole family, keeping all family members on board. It has also invested in digital applications and resources to increase the efficiency of operations, profile the producers and their products, and facilitate engagement with markets and customers.